Solid state fermentation (SSF) of sago starch for kojic acid production - Khatijah, Binti Basri (University Malaysia Sarawak (UNIMAS), 2013)
Malaysia produces an abundant supply of sago starch particularly in Sarawak. Owing to its starch content, sago starch can be used to produce kojic acid. Kojic acid is one of the highly demanded organic acids due to its extensive applications in medical, agriculture, food, cosmetic and chemistry. In this work, the potential of A. flavus NSH9 in producing kojic acid and the optimum conditions of kojic acid production from sago starch by A. flavus NSH9 via SSF was identifed. The optimum initial moisture content was found at 60% initial moisture content and the optimum inoculum size for kojic acid production obtained from this study was 108 spores/ ml. On the other hand, the optimum pH level for maximum kojic acid production from sago starch as sought from this study was pH2.5. Meanwhile, the optimal range of incubation period for kojic acid production from sago starch via SSF was identified between 8 and 18 days. The feasibility of the present research work demonstrated the promising potentiality of sago starch as alternative substrate for kojic acid production by A. flavus NSH9 via SSF.